Vocational Rehabilitation for Persons With Visual Impairment at the Community: A Case Study in Dong Da District, Hanoi City, Vietnam - Tung, Trinh Van; Nhung, Le Thi; Ha, Bui Ngoc; Hoai, Nguyen Thi Thu (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Work has been emphasized by the WHO, ILO, and UNESCO for years as to how individuals can escape poverty, secure the necessities and improve his/her economic and social status. In this sense, vocational rehabilitation is regarded as the means for persons with disabilities to access work. However, in the absence of either these programs or full respect for their right to work, they have been encountering different barriers in employment accessibility. This happens more seriously in developing countries, including Vietnam. Through mixed methods of desktop reviews, a survey with 110 persons with visual impairment in the community, and in-depth interviews with 10 key stakeholders, the article aims at briefing an overview on current situations of their employment as well as vocational rehabilitation services and support for occupations in Dong Da District, Hanoi City. Several key findings indicate that they have been coping with unemployment or low-tech and low-paid jobs. There is an intensive gap between needs and service supplies in physical, cognitive, and psychosocial components. In the community, available programs target supporting them in terms of physical aspects rather than cognitive and social components. Finally, the authors discuss more various vocational programs, capacity building to other potential providers, and awareness-raising.